Impact of gender on the clinical presentation and diagnosis of deep-vein thrombosis - Bauersachs, Rupert M.; Riess, Hanno; Hach-Wunderle, Viola; Gerlach, Horst; Carnarius, Heike; Eberle, Sonja; Rabe, Eberhard; Schellong, Sebastian M. (Thrombosis and Haemostasis, 2010)
It is uncertain whether gender influences the clinical presentation of deep-vein thrombosis (DVT) and the discriminative value of the Wells diagnostic pretest probability score. The aim of the study was to determine whether gender impacts the clinical presentation and diagnosis of DVT. The study analysed a cohort of 4,976 outpatients with clinically suspected DVT of the leg prospectively recruited by 326 vascular medicine physicians in the German ambulatory care sector between October and December 2005. The diagnosis of DVT was based on compression ultrasonography in 96% of patients. Among 4,777 patients who had a diagnostic work-up for DVT there were more women (n=2,998) than men (n=1,779). However, the prevalence of confirmed DVT was 37.0% (658/1779) in men vs. 24.3% (730/2,998) in women (p<0.001). Among patients with confirmed DVT, proximal DVT was more common in men (59.6% vs. 44.5% in women, p<0.001). Swelling of the leg, pitting oedema and dilated superficial veins were more frequently reported by men (p<0.001). The percentage of patients with a high probability Wells clinical pretest score was higher in men than in women (67.0% vs. 57.0%, p<0.001). However, overall, the score equally discriminated risk groups for DVT in both sexes. In conclusion, women were more frequently referred for a diagnostic work-up for DVT than men, but the prevalence of DVT was higher in men and their thrombotic events were more severe. Nevertheless, the Wells clinical pretest probability score correctly identified low- and high-risk groups in both genders.
Keywords: Clinical presentation; deep-vein thrombosis; diagnosis; gender; Wells score